Розвідки сучасного українсько-канадського фольклору: погляд з Вінніпега - Климаш, Р. (Народна творчість та етнологія, 2012)
Robert-Bohdan Klymasz. Survey of Contemporary Folklore of Canadian Ukrainians: View from Winnipeg. This article deals with the contemporary folklore of Canadian Ukrainians, especially with the new forms of tradition in the urban surroundings.